Triple-negative breast cancer is associated with EGFR, CK5/6 and c-KIT expression in Malaysian women - Kanapathy Pillai, Shant Kishen (BioMed Central, 2012)
BACKGROUND: Triple-negative breast cancer (TNBC) is a heterogeneous subgroup of breast cancer characterized by the lack of estrogen receptor (ER), progesterone receptor (PR) and the human epidermal growth factor receptor 2 (HER2) expressions. This subgroup of refractory disease tends to have aggressive clinical behavior, high frequency of metastasis and lack of response to current hormonal or targeted therapies. Despite numerous studies reporting the clinicopathological features of TNBC and its association with the basal-like phenotype in the Western population, only limited data are available in the Asian population. Therefore, the aim of this study was to investigate the clinicopathological characteristics of TNBC and its association with epidermal growth factor receptor (EGFR), cytokeratin 5/6 (CK5/6) and mast/stem cell growth factor receptor (c-KIT or CD117) expression in Malaysian women. METHODS: A total of 340 patients diagnosed with primary breast cancer between 2002 and 2006 in Malaysia were reviewed and analyzed. RESULTS: The incidence of TNBC was 12.4% (42/340). Bivariate analysis revealed that TNBC was strongly associated with a younger age, higher grade tumor and p53 expression. Further immunohistochemical analysis suggested that TNBC in Malaysian women was strongly associated with EGFR, CK5/6 and c-KIT expression with high a Ki-67 proliferation index. CONCLUSION: In conclusion, our study confirms the association of TNBC with basal-like marker expression (EGFR, CK5/6 and c-KIT) in Malaysian women, consistent with studies in other populations.